Software Project Effort Estimation Foundations and Best Practice Guidelines for Success - Trendowicz, Adam.; Jeffery, Ross.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Software effort estimation is one of the oldest and most important problems in software project management, and thus today there are a large number of models, each with its own unique strengths and weaknesses in general, and even more importantly, in relation to the environment and context in which it is to be applied. Trendowicz and Jeffery present a comprehensive look at the principles of software effort estimation and support software practitioners in systematically selecting and applying the most suitable effort estimation approach. Their book not only presents what approach to take and how to apply and improve it, but also explains why certain approaches should be used in specific project situations. Moreover, it explains popular estimation methods, summarizes estimation best-practices, and provides guidelines for continuously improving estimation capability. Additionally, the book offers invaluable insights into project management in general, discussing issues including project trade-offs, risk assessment, and organizational learning. Overall, the authors deliver an essential reference work for software practitioners responsible for software effort estimation and planning in their daily work and who want to improve their estimation skills. At the same time, for lecturers and students the book can serve as the basis of a course in software processes, software estimation, or project management.
PART I Foundations -- Challenges of Predictable Software Development -- Principles of Effort and Cost Estimation -- Common Factors Influencing Software Project Effort -- Estimation under Uncertainty -- Basic Estimation Strategies -- PART II Selecting An Appropriate Estimation Method -- Classification of Effort Estimation Methods -- Finding the Most Suitable Estimation Method -- PART III Popular Effort Estimation Methods -- Statistical Regression Analysis -- Constructive Cost Model – COCOMO -- Classification and Regression Trees -- Case-Based Reasoning -- Wideband Delphi -- Planning Poker -- Bayesian Belief Networks – BBN -- CoBRA -- PART IV Establishing Sustainable Effort Estimation -- Continuously Improving Effort Estimation -- Effort Estimation Best Practices -- Appendix.
Keywords: Software engineering; Management information systems; Computer science; Project management; Software Engineering; Management of Computing and Information Systems; Project Management; Software Management